Impact of 10% vs. 5% immunoglobulin products on treatment outcomes in Kawasaki disease: a multicenter retrospective study - Daichi Sajiki; Nobuhiro Nishio; Taichi Kato; Takashi Hirao; Kentaro Suzuki; Kiyotaka Go; Fumie Kinoshita; Hiroyuki Kidokoro; Jun-ichi Kawada; Yoshiaki Sato; Yoshiyuki Takahashi (Scientific Reports)
Abstract Kawasaki disease (KD) is an acute vasculitis predominantly affecting younger children, and intravenous immunoglobulin (IVIG) treatment can reduce coronary artery lesion (CAL) development. This multicenter retrospective study aimed to evaluate whether using 10% immunoglobulin products, which allow for faster IVIG administration than conventional 5% immunoglobulin products, impact KD treatment outcomes. We analyzed data of 496 patients with KD from nine Japanese hospitals, divided into 5% (n = 247) and 10% (n = 249) immunoglobulin groups. The results show that the 10% immunoglobulin group had a shorter duration of IVIG infusion compared to the 5% group (12.9 vs. 24.3 h, P < 0.001) but had a lower cumulative incidence of fever resolution 24 h after starting IVIG (66.7% vs. 77.7%, P = 0.023), and the difference was maintained thereafter. The 10% group also had more IVIG nonresponders (24% vs. 17%, P = 0.046). There were no significant differences in the interval between primary and secondary treatment or in the incidence of CALs and severe adverse events. These findings suggest that while 10% immunoglobulin products facilitate faster IVIG administration, they may lead to increased nonresponse rates, highlighting the need for further studies to optimize KD treatment protocols, such as duration of IVIG administration.